Leptospirose bovina: sorogrupos mais predominantes no município de Novo Repartimento, Pará - Guedes, I. B.; Araújo, S. A. A.; Souza, G. O.; Castro, J. F. P.; Souza-Filho, A. F.; Heinemann, M. B. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
In cattle, leptospirosis is particularly manifested by reproductive disorders, leading to losses in the production of these animals. Once the disease is present in a herd, control becomes difficult, especially by the adaptation of the bacterium to the animal species and can become a reservoir and/or maintenance host, such as serovars of the Sejroe serogroup for cattle.